The Fundamental Comparison of Zn-2Mg and Mg-4Y-3RE Alloys as a Perspective Biodegradable Materials - Kubásek, Jiří; Dvorský, Drahomír; Šedý, Jiří; Msallamová, Šárka; Levorová, Jitka; Foltán, René; Vojtěch, Dalibor (Materials (Basel, Switzerland), 2019)
Biodegradable materials are of interest for temporary medical implants like stents for restoring damaged blood vessels, plates, screws, nails for fixing fractured bones. In the present paper new biodegradable Zn-2Mg alloy prepared by conventional casting and hot extrusion was tested in in vitro and in vivo conditions. Structure characterization and mechanical properties in tension and compression have been evaluated. For in vivo tests, hemispherical implants were placed into a rat cranium. Visual observation of the living animals, an inspection of implant location and computed tomography CT imaging 12 weeks after implantation were performed. Extracted implants were studied using scanning electron microscopy (SEM) on perpendicular cuts through corrosion products. The behaviour of zinc alloy both in in vitro and in vivo conditions was compared with commercially used Mg-based alloy (Mg-4Y-3RE) prepared by conventional casting and hot extrusion. Both compressive and tensile yield strengths of Zn and Mg-based alloys were similar; however, the brittleness of Mg-4Y-3RE was lower. Zn and Mg-based implants have no adverse effects on the behaviour or physical condition of rats. Moreover, gas bubbles and the inflammatory reaction of the living tissue were not detected after the 12-week period.
Keywords: corrosion; in-vivo tests; magnesium; biodegradable materials; zinc